Does malaga city have green and blue infraestructures? analysis of their ecological connectivity, population accesibility and potential ecosystem services - Luque Florido, Adrián; Hueso-González, Paloma; Martínez-Murillo, Juan Francisco (My University, 2018)
Ecosystem services (ES) are defined as “benefits people obtain from ecosystems”, and classified as provisioning, regulation and maintenance, and cultural services. Nowadays, there is continuous search for incrementing wellbeing, besides a higher concern for environment. Accordingly, ES contribute positively to decrease these concerns. Green and blue infrastructures (GBI) play an important role in the regulation of natural cycles in urban and periurban areas, providing a number of ES, not always considered in planning and decision making process. GBI may be designed to reduce the ecological footprint, reduce natural hazards, and improve the quality of urban living environment (e.g air quality, water quality, noise, climate, aesthetics). GBI provide space for relaxation and restoration as well as exercise and leisure activities, promote new green services and jobs, and therefore increase the resilience of cities facing the Global Change. Many Mediterranean cities present few spaces considered as GBI. In our case study, does Málaga city have GBI providing ES to its population? Málaga is a Mediterranean city of importance in southern Europe due to its strategic location and good communications. It has a population of almost 600.000 people plus the great amount of tourist throughout the year. Thus, it would be rather important to have GBI improving urban quality life and well-being.
Keywords: Ecosistemas; Málaga; Servicios ecosistémicos; Infraestructuras verdes; Población